Low level of local wisdom-based biology education research: What should we do? - Ahmad Fauzi; Bea Hana Siswati; Shefa Dwijayanti Ramadani (University of Muhammadiyah Malang, 2024)
Research on local wisdom-based biology education is increasingly important in efforts to enrich the national curriculum and preserve Indonesia's cultural heritage. However, systematic studies on trends and varieties of research in this field are still limited. This study aims to analyze trends in local wisdom-based biology education research in Indonesia using data from SINTA 1 to 3 accredited journals during the period 2013-2022. Using a systematic search method, 77 articles related to local wisdom from 22 journals were identified. The analysis shows that although the number of articles has increased from year to year, the percentage of publications focusing on local wisdom is still low. This study also identified a variety of research designs, development models, measured data, and diverse research areas. These findings highlight the need for increased attention to local wisdom-based research in biology education and the development of more standardized instruments to support the sustainability and integration of local wisdom in education. These results are expected to be a reference for researchers and educators in developing a curriculum that is contextual and relevant to local wisdom in Indonesia.